Interaction between dissolved organic carbon and fungal network governs carbon mineralization in paddy soil under co-incorporation of green manure and biochar - Cheng, Kun; Wang, Xiaoyue; Fu, Libo; Wang, Wei; Liu, Ming; Sun, Bo (Frontiers in Microbiology, 2023)
Legume crops in rice cultivation are typically rotated and incorporated into soil as green manure to improve soil fertility. Biochar has recently been co-incorporated with green manure to simultaneously stimulate soil organic carbon (SOC) mineralization and increase carbon (C) sequestration. However, few studies examine effects of co-incorporation of biochar and green manure on C cycling and the underlying microbial mechanisms in paddy fields. In this study, the effects of co-incorporation of green manure and biochar on C mineralization, dissolved organic carbon (DOC) characteristics, and microbial community structures were investigated. A pot study was conducted with three treatments: inorganic NPK (NPK), inorganic NPK + green manure (GM), and inorganic NPK + green manure + biochar (GMC). Organic amendments significantly increased cumulative C mineralization, with amounts in the order GMC (3434 mg• kg -1 ) > GM (2934 mg• kg -1 ) > NPK (2592 mg• kg -1 ). Fertilizer treatments had similar effects on DOC concentrations, with amounts in the order GMC (279 mg• kg -1 ) > GM (255 mg• kg -1 ) > NPK (193 mg• kg -1 ). According to fluorescence spectra, the highest microbial humic acid-like fraction and biological index were also in GMC. Co-incorporation of green manure and biochar shifted composition of bacterial and fungal communities but more importantly, increased fungal network complexity and decreased bacterial network complexity. The increase in fungal network complexity with the increase in DOC concentrations and microbially derived components was the dominant factor in promoting C mineralization. Overall, this study reveals the underlying biochemical mechanism, the interaction between DOC and fungal network of C cycling in paddy soil under the co-incorporation of green manure and biochar management, and provides fundamental knowledge for exploring effective approaches to improve soil fertility and health in future.